Macroeconomic Factors and Entrepreneurship in Nigeria - Dutse, A Y; Aliyu, Ibrahim (International Journal of Business and Management Future, 2017)
Provision of conducives environment to enhance the supply and sustainability of entrepreneurs has developed into a field of competition among countries of the world. In this respect, macroeconomic factors such as FBI, technology, power generation, trade openness etc are enhanced to boost entrepreneurship in a country. Thus, this study is designed to investigate the impact of those macroeconomic factors to entrepreneurship in Nigeria. Secondary data from World Bank data bank between 2006-2015 were used for the study and analyzed using STATA package. The Regression output revealed that most Nigerian macroeconomic factors have insignificant impact on the development of entrepreneurship in the country. It was therefore, recommended that, policy makers should pay attention to not only the volume of the macroeconomic factors but also their rhythm with entrepreneurship in the country.